The zinc finger transcriptional repressor Blimp1/Prdm1 is dispensable for early axis formation but is required for specification of primordial germ cells in the mouse. - Vincent, S; Dunn, N; Sciammas, R; Shapiro-Shalef, M; Davis, M; Calame, K; Bikoff, E; Robertson, E (2005)
Blimp1, a zinc-finger containing DNA-binding transcriptional repressor, functions as a master regulator of B cell terminal differentiation. Considerable evidence suggests that Blimp1 is required for the establishment of anteroposterior axis formation and the formation of head structures during early vertebrate development. In mouse embryos, Blimp1 is strongly expressed in axial mesendoderm, the tissue known to provide anterior patterning signals during gastrulation. Here, we describe for the first time the defects caused by loss of Blimp1 function in the mouse. Blimp1 deficient embryos die at mid-gestation, but surprisingly early axis formation, anterior patterning and neural crest formation proceed normally. Rather, loss of Blimp1 expression disrupts morphogenesis of the caudal branchial arches and leads to a failure to correctly elaborate the labyrinthine layer of the placenta. Blimp1 mutant embryos also show widespread blood leakage and tissue apoptosis, and, strikingly, Blimp1 homozygous mutants entirely lack PGCs. At the time of PGC allocation around 7.25 days post coitum, Blimp1 heterozygous embryos exhibit decreased numbers of PCGs. Thus Blimp1 probably acts to turn off the default pathway that allows epiblast cells to adopt a somatic cell fate, and shifts the transcriptional program so that they become exclusively allocated into the germ cell lineage.